Characterization and in vitro spread of mesquite (Prosopis laevigata (Humb. & Bonpl. ex Willd.) M.C.Johnst.) (Agro Productividad, 2022)
Objective: To analyze fruit characteristics, genetic diversity, and in vitro spread of mesquite genotypes (Prosopis laevigata (Humb. & Bonpl.) ex Willd.) from the plains of Ojuelos-Aguascalientes, Mexico.Design/Methodology/Approach: Fruit and leaf samples were collected from 20 mesquite genotypes to analyze and extract DNA to determine their diversity using RAPDs. Simultaneously, in vitro spread tests were performed.Results: The Ojuelos de Jalisco genotype stood out for the weight of its fruits, while La Presa genotype stood out for its degrees Brix. Genotypes were grouped according to their best growth condition for their genetic analysis. In in vitro spread, AG3 with IBA allowed stem/shoot elongation and root formation; meanwhile, AgNO3 prevents leaf fall, allowing rooting and transfer to the soil.Study Implications/Limitations: This study about mesquite (P. laevigata) was limited to the plains of Ojuelos-Aguascalientes.Findings/Conclusions: Mesquite plants from the Ojuelos-Aguascalientes subregion, Mexico, were identified and georeferenced; likewise, a methodology for its in vitro spread was developed.